Solid electrolyte, method for preparing the same, and secondary battery comprising the same
By using solid electrolyte with a porous layer structure in lithium secondary batteries, the problems of lithium penetration and interface resistance in lithium secondary batteries are solved, higher ion conductivity and mechanical strength are achieved, and the battery life is extended.
Patent Information
- Application Number
- CN201910500163.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-06
- Filing Date
- 2019-06-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2039-06-11
AI Technical Summary
When an inorganic solid electrolyte is used in existing lithium secondary batteries, the interface resistance between the lithium metal electrode and the solid electrolyte increases, and lithium penetrates into the grain boundary of the inorganic solid electrolyte easily leads to a short circuit, affecting the stability and performance of the battery.
Using a solid electrolyte including an inorganic lithium ion conductive film and a porous layer, the porous layer consists of a first porous layer and a second porous layer, the pore size of the first porous layer is larger than that of the second porous layer, and is treated and cleaned by acid. A porous structure is formed to increase the surface area of the electrolyte to reduce interface resistance and inhibit lithium penetration.
It effectively reduces the interface resistance of lithium secondary batteries, improves the ion conductivity and mechanical strength of the battery, extends the cycle life of the battery, and improves the charging and discharging performance of the battery.
Smart Images

Figure CN110880616B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-106504 filed in the Korean Intellectual Property Office on September 6, 2018 and all rights arising therefrom, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present disclosure relates to a solid electrolyte for a secondary battery, a method for preparing the same, and a secondary battery including the same. Background Art
[0004] With the explosive growth of reusable energy storage devices applicable to electric vehicles and portable electronic devices, there is a growing demand for lithium secondary batteries with high capacity and improved stability. Lithium metal electrodes as negative electrodes for lithium secondary batteries have been studied as options to increase charge storage capacity and provide secondary batteries with high voltage.
[0005] However, when an inorganic solid electrolyte is used as an electrolyte in a lithium secondary battery including a lithium metal electrode, a short circuit may occur due to penetration of lithium into a grain boundary of the inorganic solid electrolyte, and an interface resistance between the lithium metal electrode and the solid electrolyte may increase.
[0006] Therefore, there remains a need for improved solid electrolytes for lithium secondary batteries. Summary of the invention
[0007] Provided are a solid electrolyte and a method for preparing the same.
[0008] A secondary battery including the solid electrolyte is provided.
[0009] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments.
[0010] According to an aspect of one embodiment, a solid electrolyte includes an inorganic lithium ion conductive membrane and a porous layer on a surface of the inorganic lithium ion conductive membrane, wherein the porous layer includes a first porous layer and a second porous layer, and the second porous layer is arranged between the inorganic lithium ion conductive membrane and the first porous layer, and wherein the first porous layer has a pore size (pore diameter) larger than the pore size of the second porous layer.
[0011] According to an aspect of another embodiment, a secondary battery includes a positive electrode, a negative electrode, and the solid electrolyte interposed between the positive electrode and the negative electrode.
[0012] According to an aspect of another embodiment, a method for preparing a solid electrolyte includes: a first acid treatment, which includes acid-treating an inorganic lithium ion conductive membrane with an acid having a concentration greater than 0.1 molar concentration (M) and less than or equal to about 5 molar concentration to provide a first acid-treated product; and a first cleaning, which includes cleaning the first acid-treated product to provide a cleaned first acid-treated product to prepare the solid electrolyte.
[0013] The inorganic lithium ion conductive membrane may be prepared by mixing an inorganic lithium ion conductor and a lithium compound to prepare a mixture, and heat-treating the mixture.
[0014] The method further includes: a second acid treatment, which includes acid-treating the washed first acid-treated product with an acid having a concentration greater than 0.1 M and less than 5 M to provide a second acid-treated product; and a second washing process, which includes washing the second acid-treated product.
[0015] According to an aspect of another embodiment, a method for preparing a solid electrolyte includes forming a multilayer film on the surface of an inorganic lithium ion conductive membrane, the formation comprising: coating a first composition including a pore former and a lithium ion conductor on the surface of the inorganic lithium ion conductive membrane, and drying the first composition, coating a second composition including a pore former and a lithium ion conductor on the dried first composition, and drying the second composition to form a multilayer film, and heat treating the multilayer film to prepare the solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] These and / or other aspects will become apparent and more readily appreciated from the following description of the embodiments considered in conjunction with the accompanying drawings, in which:
[0017] Figure 1 A schematic diagram for explaining an embodiment of a structure according to a solid electrolyte;
[0018] Figure 2 A schematic diagram for explaining another embodiment of the structure of a solid electrolyte;
[0019] Figure 3 A schematic diagram for explaining an embodiment of a structure of a secondary battery;
[0020] Figure 4A is a scanning electron microscope (SEM) image of a cross section of a solid electrolyte prepared according to Example 1, wherein the horizontal dotted lines depict the layered structure;
[0021] Figure 4B for Figure 4A The enlarged area of the circled portion of the image;
[0022] Figure 4Cis a SEM image of a cross section of a solid electrolyte prepared according to Comparative Preparation Example 1-1, wherein the dotted line depicts a layered structure;
[0023] Figure 5A is a graph of cumulative intrusion (mL / g) versus pore diameter (μm), illustrating pore size distribution and mechanical strength (Ring on Ring test) of solid electrolytes prepared according to Examples 6 and 7;
[0024] Figure 5B is a graph of incremental intrusion (mL / g) versus pore diameter (μm), illustrating the pore size distribution and mechanical strength (ring-on-ring test) of the solid electrolyte prepared according to Comparative Example 2;
[0025] Fig. 6A are graphs of counts (arbitrary units) versus diffraction angle (degrees, 2θ), which illustrate the results of X-ray diffraction (XRD) analysis of the LLZO film prepared according to Preparation Example 1 and the solid electrolyte prepared according to Example 1, respectively;
[0026] Figure 6B for Fig. 6A An enlarged portion of the circled portion of ;
[0027] Fig. 7A and 7B is the imaginary impedance (-Z", ohm cm 2 ) for the real impedance (Z', ohm cm 2 ) which respectively illustrate the impedance characteristics of the lithium secondary batteries prepared according to Example 8 and Comparative Example 3;
[0028] Figures 8A-8C is the electrode potential (V, relative to Li / Li + ) for capacity (milliampere-hour / square centimeter, mAh·cm -2 ) which respectively illustrate the charge / discharge characteristics of lithium secondary batteries prepared according to Example 8 and Comparative Examples 3 and 4;
[0029] Fig.9A is the capacity (mAh·cm -2 ) and efficiency (percent, %) versus cycle number, which illustrates the capacity and efficiency of the lithium secondary battery prepared according to Example 8;
[0030] Fig. 9B is the electrode potential (V, relative to Li / Li + ) vs. Capacity (mAh·cm -2 ) which illustrates the electrode potential of the lithium secondary battery prepared according to Example 8;
[0031] Fig. 9C is the capacity (mAh·cm -2 ) versus cycle number, illustrating the capacity of the lithium secondary battery prepared according to Comparative Example 8;
[0032] Figures 10A-10C are graphs of intensity (arbitrary unit, au) versus binding energy (electron volt, eV), which respectively illustrate the results of Li 1s, C 1s, and O 1s X-ray photoelectron spectroscopy (XPS) analysis of the LLZO film prepared according to Preparation Example 1;
[0033] Figures 10D-10F are graphs of intensity (au) versus binding energy (eV), which illustrate the results of Li 1s, C 1s, and O 1s XPS analysis of the solid electrolyte prepared according to Example 1, respectively;
[0034] Fig.11A and 11B is the imaginary impedance (-Z", ohm cm 2 ) for the real impedance (Z', ohm cm 2 ) illustrate the impedance results of Evaluation Example 7, which are aging tests of lithium secondary batteries prepared according to Comparative Example 3 and Example 8;
[0035] Fig. 12A A bar graph illustrating the relative amounts of protons at the surface and within the solid electrolyte for Example 1 and the solid electrolyte of Preparation Example 1, which illustrates the results of laser induced breakdown spectroscopy (LIBS) analysis of the solid electrolyte prepared according to Example 1 and the LLZO film prepared according to Preparation Example 1;
[0036] Fig. 12B is a graph of the relative amount of protons versus the distance from the surface (micrometer, μm), which illustrates the results of LIBS analysis of the solid electrolyte prepared according to Example 1 and the LLZO membrane prepared according to Preparation Example 1;
[0037] Fig.13A and 13B is the electrode potential (V, relative to Li / Li + ) vs. Capacity (mAh·cm -2 ) which illustrates the electrode potential relative to the capacity of the lithium secondary batteries prepared according to Examples 8 and 11; and
[0038] Fig.14A and 14B is the electrode potential (V, relative to Li / Li + ) vs. Capacity (mAh·cm -2) which illustrates the electrode potentials of the lithium secondary batteries prepared according to Comparative Examples 6 and 7. DETAILED DESCRIPTION
[0039] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals refer to the same elements throughout. In this regard, the present embodiments may have different forms and should not be construed as being limited to the descriptions set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate various aspects.
[0040] It will be understood that when an element is referred to as being “on” another element, it can be “directly on” the other element or intervening layers may be present therebetween. In contrast, when an element is referred to as being “directly on” another element, there are no intervening elements present.
[0041] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to be limiting. As used herein, the singular forms "a, an" and "the" are intended to include plural forms, including "at least one", unless the content clearly states otherwise. "At least one" is not to be interpreted as limiting "one". As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items. Expressions such as "at least one of..." when before or after a list of elements modify the entire list of elements without modifying the individual elements of the list.
[0042] As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items. It will be further understood that the term "include" or "comprises" when used in this specification means the presence of the described features, regions, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more additional features, regions, wholes, steps, operations, elements, components and / or their collections.
[0043] For ease of description, spatially relative terms such as "under", "below", "lower", "above", "upper", etc. may be used herein to describe the relationship of one element or feature to another element or feature as shown in the figure. It will be understood that in addition to the orientation depicted in the figure, the spatially relative terms are also intended to include different orientations of the device in use or operation. For example, if the device in the figure is flipped, the elements described as "under" or "below" other elements or features will be oriented "above" other elements or features. Therefore, the exemplary term "under" can include both above and below. The device can be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative descriptors used in this article are interpreted accordingly.
[0044] As used herein, "about" or "approximately" is inclusive of the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations of the stated value, or within ±20%, 10%, or 5%.
[0045] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as their meanings consistent with their meanings in the context of the relevant art and the present disclosure, and will not be interpreted in an idealized or overly formal sense unless clearly defined in this article.
[0046] Hereinafter, a solid electrolyte, a method for preparing the same, and a secondary battery including the solid electrolyte will be described.
[0047] A solid electrolyte according to an embodiment includes an inorganic lithium ion conductive membrane and a porous layer on a surface of the inorganic lithium ion conductive membrane, wherein the porous layer includes a first porous layer and a second porous layer, and the second porous layer is arranged between the inorganic lithium ion conductive membrane and the first porous layer, wherein the first porous layer has a pore size larger than a pore size of the second porous layer.
[0048] The first porous layer on the second porous layer and opposite (opposite) to the inorganic ion conductive membrane may have a porosity greater than the porosity of the second porous layer located between the first porous layer and the inorganic lithium ion conductive membrane. The porous layer may have a structure in which the pore size gradually increases in the thickness direction of the solid electrolyte. The pore size may increase linearly or nonlinearly in the thickness direction. More specifically, the pore size of the porous layer gradually increases in the direction from the inorganic lithium ion conductive membrane to the outer surface of the porous layer. When the porosity gradient or pore size gradient of the solid electrolyte is as described above, the solid electrolyte may have improved ion conductivity and mechanical strength. As used herein, the term "thickness direction" refers to the direction from the inorganic lithium ion conductive membrane 11 to the opposite surface of the solid electrolyte, such as Figure 1 as shown in .
[0049] Inorganic solid electrolytes can be used as electrolytes in lithium secondary batteries including lithium metal electrodes. When using inorganic solid electrolytes, lithium penetration into the grain boundaries of the inorganic solid electrolyte can occur. As a result, lithium ion conductivity can be reduced at the grain boundaries, short circuits can occur due to lithium plating on or in the grain boundaries, and the resistance of the battery can increase due to the interface resistance between the lithium metal electrode and the solid electrolyte.
[0050] The present inventors have developed a solid electrolyte comprising a porous layer located on at least one surface thereof, wherein the pore size at the surface of the porous layer is greater than the pore size inside the porous layer. In an embodiment, the region of the porous layer located on the surface of the solid electrolyte may have a porosity greater than that of another region of the porous layer located inside the solid electrolyte. In the solid electrolyte, when the pore size and porosity at the surface are greater than those in the interior of the porous layer as described above, the contact area between the electrode in contact with the solid electrolyte and the solid electrolyte increases, thereby reducing the interface resistance. Therefore, since the surface of the solid electrolyte has a porous structure having a large surface area, the stress of the electrodeposited lithium metal, such as the electrodeposited lithium at a high current density, may not be concentrated in a local region of the solid electrolyte, such as at a defect. In addition, lithium can be inhibited from penetrating into the grain boundary.
[0051] Will refer to Figure 1 and 2 The structure of the solid electrolyte according to the embodiment is further described.
[0052] Figure 1 The solid electrolyte 10 shown in the figure includes an inorganic lithium ion conductive membrane 11 and a porous layer 14 located thereon. The porous layer 14 includes a first porous layer 13 located on the surface of the solid electrolyte 10 and a second porous layer 12 located between the inorganic lithium ion conductive membrane 11 and the first porous layer 13. The pore size of the first porous layer 13 is larger than the pore size of the second porous layer 12. The porosity of the first porous layer 13 may be greater than the porosity of the second porous layer 12. The inorganic lithium ion conductive membrane 11 of the solid electrolyte 10 excluding the porous layer 14 forms a dense portion, has ion conductivity, blocks the movement of substances other than ions between the positive electrode and the negative electrode, and inhibits the penetration of lithium dendrites. In Figure 1 In FIG. 1 , the arrow indicates the thickness direction of the solid electrolyte 10 .
[0053] Figure 2 The solid electrolyte 10 and Figure 1 The third porous layer 15 having a pore size smaller than that of the second porous layer 12 is disposed between the second porous layer 12 and the lithium ion conductive membrane 11. The pore size of the first porous layer 13 is larger than that of the second porous layer 12.
[0054] The porosity of the third porous layer 15 may be adjusted to be smaller than the porosity of the second porous layer 12 , and the porosity of the second porous layer 12 may be adjusted to be smaller than the porosity of the first porous layer 13 .
[0055] The solid electrolyte 10 may have a structure in which the pore size gradually increases in the thickness direction. Figure 1 The solid electrolyte 10 and Figure 2 The porous layers of the solid electrolyte 10 have a double-layer structure and a triple-layer structure, respectively. The solid electrolyte may also have a multilayer structure including at least three layers.
[0056] exist Figure 1 In the embodiment of the present invention, the first porous layer 13 may include, consist essentially of, or consist of macropores, and the second porous layer 12 may include, consist essentially of, or consist of micropores. As used herein, the term "macropore" refers to a pore having a diameter greater than or equal to about 10 microns, such as 10 microns to 1000 microns, or a maximum dimension such as a length or width dimension, and the term "micropore" refers to a pore having a diameter less than about 10 microns, such as 0.01 microns to less than 10 microns, or a maximum dimension such as a length or width dimension. Although the thickness ratio of the first porous layer 13 to the second porous layer 12 is not particularly limited, the thickness ratio may be about 0.1:1-about 1:1, or about 0.2:1-about 1:1, or about 0.5:1-about 1:1.
[0057] The first porous layer 13 may include open pores. When the first porous layer 13 includes open pores, the surface area of the solid electrolyte is effectively increased, thereby improving the adhesion between the solid electrolyte 10 and the electrode. The second porous layer 12 may include closed pores. When the second porous layer 12 includes closed pores, the ion conductivity of the solid electrolyte may be increased.
[0058] The total thickness and density of the porous layer located on the surface and inside of the solid electrolyte can be selected to prevent liquid from penetrating the solid electrolyte. In an embodiment, the porous layer has a total thickness and density that makes the solid electrolyte impermeable to liquid. The total thickness of the porous layer may be about 5%-about 95%, about 10%-about 90%, or about 15%-about 85% based on the total thickness of the solid electrolyte. When the percentage of the porous layer of the total thickness of the solid electrolyte is within this range, the relatively dense portion of the solid electrolyte (i.e., i) the area of the solid electrolyte closest to the inorganic lithium ion conductive membrane or ii) the area of the solid electrolyte other than the porous layer) can completely prevent the penetration of electrode components such as lithium dendrites, and the many ion conductive paths formed in the porous layer can increase the battery capacity and increase the output power.
[0059] The total thickness of the solid electrolyte may be about 10 micrometers (μm) to about 500 μm, or about 30 μm to about 400 μm, or for example about 40 μm to about 300 μm. The thickness of the porous layer 14 may be about 1 μm to about 475 μm, or about 5 μm to about 250 μm, or about 10 μm to about 100 μm, or for example about 10 μm to about 30 μm.
[0060] Figure 1 The porous layer 14 of the solid electrolyte 10 shown in the figure may have an average pore size of about 0.1 μm to about 1000 μm, for example, about 0.1 μm to about 500 μm, for example, about 1 μm to about 50 μm, or about 1 μm to about 35 μm. The first porous layer 13 located on the surface of the solid electrolyte 10 may have an average pore size of about 10 μm to about 500 μm, or about 10 μm to about 100 μm, or about 15 μm to about 35 μm. The second porous layer 12 located inside the solid electrolyte 10 may have an average pore size of about 0.1 μm to about 10 μm, or about 0.5 μm to about 7.5 μm, or about 1 μm to about 5 μm.
[0061] The porous layer 14 may have a porosity of about 5% to about 70%. The first porous layer 13 located on the surface of the solid electrolyte 10 may have a porosity of about 30% to about 80%, or about 40% to about 75%, or about 50% to about 75%, and the second porous layer 12 located inside the solid electrolyte 10 may have a porosity of about 1% to about 40%, or about 1% to about 30%, or about 1% to about 25%.
[0062] The first porous layer 13 may include open pores open to the outside of the porous layer 14. The first porous layer 13 may have an open porosity of about 30% or more, or about 35% or more, or about 40% or more, for example, about 30% to about 90%, or about 30% to about 50%, or about 50% to about 90%. The open porosity of the first porous layer 13 refers to the percentage of the volume of the open pores in the first porous layer 13 relative to the total pore volume of the first porous layer 13 or relative to the total volume of the first porous layer 13. When the open porosity of the first porous layer 13 is about 30% or more, intrusion of the electrode active material into the first porous layer 13 in the case where the electrode active material layer is formed on the first porous layer 13 can be improved. As a result, the contact area between the electrode active material and the first porous layer 13 can be increased, thereby further increasing the battery capacity. In addition, the first porous layer 13 may have an open porosity of about 60% to about 100%, such as about 70% to about 100%, or such as about 80% to about 100%. When the open porosity is within these ranges, most of the pores formed in the first porous layer 13 may be open pores.
[0063] exist Figure 2In the solid electrolyte 10, the porous layer 14 may have an average pore size of about 0.1 μm to about 1000 μm, such as about 0.1 μm to about 500 μm, such as about 1 μm to about 50 μm, or such as about 1 μm to about 35 μm. The porous layer 14 also has a wide pore size distribution. In addition, the first porous layer 13 located on the surface of the solid electrolyte 10 may have an average pore size of about 10 μm to about 500 μm, or about 10 μm to about 300 μm, or for example, about 15 μm to about 35 μm, the second porous layer 12 located inside the solid electrolyte 10 may have an average pore size of about 0.1 μm to about 10 μm, or about 0.5 μm to about 7.5 μm, or for example, about 1 μm to about 5 μm, and the third porous layer 15 may have an average pore size of about 0.1 μm to about 5 μm, or about 0.1 μm to about 3 μm, or for example, about 0.1 μm to about 1 μm. The porous layer 14 may have a porosity of about 5% to about 60%, and the first porous layer 13 located on the surface of the solid electrolyte 10 may have a porosity of about 5% to about 80%, and the second porous layer 12 and the third porous layer 15 located inside the solid electrolyte 10 may have porosities of about 1% to about 50% and about 1% to about 30%, respectively.
[0064] The porous layer may have an irregular or regular porous structure. The term "irregular porous structure" refers to a structure including pores having non-uniform pore sizes and non-uniform shapes.
[0065] As used herein, the term "pore size" or "average pore size" refers to the average diameter of the hole when the hole is spherical or circular. When the hole has an elliptical shape, the pore size refers to the length along the major axis. As used herein, the term "porosity" is used to refer to the measurement of the empty space (i.e., void or hole) in the material and is measured as a percentage of the volume of the void in the material based on the total volume of the material. Pore size and porosity can be measured based on cross-sectional scanning electron microscopy images or by Bruno-Emmett-Teller (BET) method. Open porosity can be calculated based on sintered density and bulk density (bulk density, volume density) such as measured by the Archimedean method.
[0066] As used herein, the term "surface of a solid electrolyte" refers to the outermost surface of a solid electrolyte, which extends a distance of about 5% to about 95%, for example, about 1% to about 40%, of the total distance from the surface of the solid electrolyte to the center of the solid electrolyte, or an area region within a distance of about 40 μm from the outermost edge of the solid electrolyte.
[0067] The term "inside the solid electrolyte" refers to the portion of the solid electrolyte directly below the surface of the solid electrolyte and continuously disposed along the surface of the solid electrolyte, and corresponds to an area extending from about 5% to about 100%, for example, 60% to about 100%, of the total distance from the outermost surface of the solid electrolyte, or the remaining area excluding the surface of the solid electrolyte or excluding the area within 40 μm from the outermost edge of the solid electrolyte.
[0068] In an embodiment, the porous layer may be permeable to liquid. In an embodiment, the dense portion of the solid electrolyte, ie, the portion not treated with acid, is not permeable to liquid.
[0069] Figure 1 At least a portion of the solid electrolyte 10 may include an inorganic lithium ion conductor containing lithium ions, and a portion of the lithium ions are replaced by protons. Figure 1 The first porous layer 13 on the surface of the solid electrolyte 10 may include a first inorganic lithium ion conductor substituted by protons of about 2% to about 100%, or about 5% to about 95%, or about 25% to about 75%, and the second porous layer 12 inside the solid electrolyte 10 may include a second inorganic lithium ion conductor substituted by protons of about 0.01% to about 20%, or about 0.05% to about 15%, or about 0.1% to about 10%.
[0070] The porous layer 14 may be a product obtained by treating an inorganic lithium ion conductive membrane with an acid having a concentration greater than 0.1 molar concentration (M) and less than or equal to about 5 M. Alternatively, the porous layer 14 may be a product obtained by forming a multilayer film on the inorganic lithium ion conductive membrane and heat-treating the multilayer film. The forming may include coating a first composition including a pore former on the surface of the inorganic lithium ion conductive membrane, and coating a second composition including a pore former on the first composition, wherein the amount of the pore former in the first composition is different from the amount of the pore former in the second composition.
[0071] The concentration of the acid may be 0.5 M to 5 M, for example 0.5 M to 4.5 M, or for example 1 M to 3 M. When the concentration of the acid is less than 0.1 M, lithium carbonate may remain in the solid electrolyte. On the contrary, when the concentration of the acid is 5 M or more, the surface of the solid electrolyte may be damaged, making it difficult to manufacture a solid electrolyte including a porous layer having a desired pore size and porosity.
[0072] By subjecting the inorganic lithium ion conductive membrane to an acid treatment or by forming a multilayer film including a pore former and heat treating the multilayer film, a portion of the inorganic lithium ion conductor can be selectively dissolved by the acid or the pore former to form a porous structure. When the porous structure is formed as described above, lithium carbonate is removed from the solid electrolyte all the way to the subsurface (subsurface), and the lithium ions of the lithium ion conductor can be replaced by protons. Moreover, the crystallinity of the solid electrolyte is improved and the average grain size is increased. As a result, the formation of metallic compounds (which can cause short circuits in secondary batteries) can be prevented, and the concentration of current can be suppressed, thereby suppressing short circuits at high current densities. In addition, due to the presence of the protonated inorganic lithium ion conductor and the increased specific surface area at the surface of the solid electrolyte, the interface resistance with the lithium metal electrode can be significantly reduced.
[0073] The lattice constant (e.g., lattice spacing) of the porous layer of the solid electrolyte as measured by X-ray diffraction (XRD) is about 0.005 angstroms greater than the lattice constant of the remaining region of the solid electrolyte excluding the porous layer. -about or about -about or about -about The average grain size of the porous layer is at least twice as large as the remaining area of the solid electrolyte excluding the porous layer. The average grain size of the solid electrolyte may be, for example, about 200 nm to about 300 nm, and its lattice constant may be about -about As used herein, "grain" means a particle or region of a particle having a single crystal direction (crystal orientation).
[0074] For example, the inorganic lithium ion conductive film of the solid electrolyte may include at least one of a garnet compound, an argyrodite compound, a lithium super ion conductor (LISICON) compound, a Na super ion conductor type (NASICON) compound, a Li nitride, a Li hydride, a perovskite, and a Li halide.
[0075] The inorganic lithium ion conductive membrane may include at least one of the following: garnet ceramic (Li 3+x La 3 M 2 O 12 , wherein 0≤x≤5, M is at least one of W, Ta, Te, Nb, or Zr), doped garnet ceramics (Li 3+x La 3 M 2 O 12, where 0 ≤ x ≤ 5, and M is at least one of W, Ta, Te, Nb, or Zr), Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (where 0 < x < 2 and 0 ≤ y < 3), BaTiO 3 、Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT)(0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O 3 -PbTiO 3 (PMN-PT), lithium phosphate (Li 3 PO 4 ), lithium titanium phosphate (Li x Ti y (PO 4 ) 3 , where 0 < x < 2, and 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO 4 ) 3 , where 0 < x < 2, 0 < y < 1, and 0 < z < 3), Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), lithium lanthanum titanate (Li x La y TiO 3 , where 0 < x < 2, and 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , where 0 < x < 4, 0 < y < 1, 0 < z < 1, and 0 < w < 5), lithium nitride (Li x N y , where 0 < x < 4, and 0 < y < 2), based on SiS 2 的玻璃(Li x Si y S z ,其中0≤x<3,0<y<2,且0<z<4)、基于P It should be noted that the text seems to be incomplete in some parts in terms of the overall context and grammar. There are some phrases like "基于P " at the end that are not fully formed. You may want to double-check the original text for accuracy.2 S 5 glass of (Li x P y S z , where 0 ≤ x < 3, 0 < y < 3, and 0 < z < 7), Li 3x La 2 / 3-x TiO 3 (0 ≤ x ≤ 1 / 6), Li 7 La 3 Zr 2 O 12 、Li 1+y Al y Ti 2-y (PO 4 ) 3 (0 ≤ y ≤ 1), Li 1+z Al z Ge 2-z (PO 4 ) 3 (where 0 ≤ z ≤ 1), Li 2 O, LiF, LiOH, Li 2 CO 3 、LiAlO 2 、Based on Li 2 O - Al 2 O 3 - SiO 2 - P 2 O 5 - TiO 2 - GeO 2 ceramics of, Li 10 GeP 2 S 12 、Li 3.25 Ge 0.25 P 0.75 S 4 、Li 3 PS 4 、Li 6 PS 5 Br, Li 6 PS 5 Cl, Li 7 PS 5 、Li 6 PS 5 I, Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 、LiTi 2 (PO 4 ) 3 、LiGe 2 (PO4 ) 3 、LiHf 2 (PO 4 ) 3 、LiZr 2 (PO 4 ) 3 、Li 2 NH、Li 3 (NH 2 ) 2 I、LiBH 4 、LiAlH 4 、Li 2 NH、Li 0.34 La 0.51 TiO 2.94 、LiSr 2 Ti 2 NbO 9 、Li 0.06 La 0.66 Ti 0.93 Al 0.03 O 3 、Li 0.34 Nd 0.55 TiO 3 、Li 2 CdCl 4 、Li 2 MgCl 4 、Li 2 ZnI 4 、Li 2 CdI 4 、Li 4.9 Ga 0.5+δ La 3 Zr 1.7 W 0.3 O 12 (where 0 ≤ δ < 1.6), Li 4.9 Ga 0.5+δ La 3 Zr 1.7 W 0.3 O 12 (where 1.7 ≤ δ ≤ 2.5), and Li 5.39 Ga 0.5+δ La 3 Zr 1.7 W 0.3 O 12 (where 0 ≤ δ < 1.11).
[0076] In the doped garnet ceramic Li 3+x La 3 M 2 O 12In the embodiment, the doping elements include Ce, Pr, Ga, Y, or a combination thereof.
[0077] The inorganic lithium ion conductive membrane may include, for example, at least one compound represented by Formula 1 or 1a.
[0078] Formula 1
[0079] Li 7-x M 1 x La 3-a M 2 a Zr 2-b M 3 b O 12
[0080] Formula 1a
[0081] Li 7-x La 3-a M 2 a Zr 2-b M 3 b O 12
[0082] Among them, in formula 1, M 1 including at least one of gallium (Ga) or aluminum (Al),
[0083] In Formulas 1 and 1a, M 2 including at least one of calcium (Ca), strontium (Sr), cesium (Cs), or barium (Ba),
[0084] M 3 including at least one of aluminum (Al), tungsten (W), niobium (Nb), or tantalum (Ta), and
[0085] 0≤x<3, 0≤a≤3, and 0≤b<2.
[0086] In Formula 1, x may be 0.01-2.1, such as 0.01-0.99, such as 0.1-0.9, and 0.2-0.8. In Formula 1, a may be 0.1-2.8, such as 0.5-2.75, and b may be 0.1-1, such as 0.25-0.5.
[0087] In the compound represented by Formula 1, the dopant may be M 1 、M 2 , or M 3 In the compound represented by Formula 1a, the dopant may be M 2 or M 3 At least one of.
[0088] As mentioned above, the following examples are as follows: Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.4 La 3 Zr 1.7 W 0.3 O 12 , Li 6.5 La 3 Zr 1.5 Ta 0.3 O 12 , Li 7 La 3 Zr 1.7 W 0.3 O 12 , Li 4.9 La 2.5 Ca 0.5 Zr 1.7 Nb 0.3 O 12 , Li 4.9 Ga 2.1 La 3 Zr 1.7 W 0.3 O 12 , Li 7 La 3 Zr 1.5 W 0.5 O 12 , Li 7 La 2.75 Ca 0.25 Zr 1.75 Nb 0.25 O 12 , Li 7 La 3 Zr 1.5 Nb 0.5 O 12 , Li 7 La 3 Zr 1.5 Ta 0.5 O 12 , Li 6.272 La 3 Zr 1.7 W 0.3 O 12 , or Li 5.39 Ga 1.61 La 3 Zr 1.7 W 0.3 O 12In the inorganic lithium ion conductive membrane, the inorganic lithium ion conductor may have a granular structure or a columnar structure. In the porous layer, the lithium ions of the inorganic lithium ion conductor may be replaced by protons, so that the amount of protons in the porous layer may be about 0.01 mol percent (mol %) to about 50 mol %, or 0.1 mol % to about 30 mol %, or, for example, about 0.1 mol % to about 20 mol %, of the total number of protons and lithium ions.
[0089] The surface of the solid electrolyte may include Li 7-x H x La 3 Zr 2-y M y O 12 (wherein 0.1≤x≤7, 0≤y≤2, and M is at least one of W, Ta, Te, or Nb), and the interior of the solid electrolyte may include Li 7-x H x La 3 Zr 2-y M y O 12 (wherein 0≤x≤6.5, 0≤y≤2, and M is at least one of W, Ta, Te, or Nb).
[0090] The surface of the solid electrolyte may include Li (7-x) H x La 3 Zr 2 O 12 (where 0.1≤x≤7), and the interior of the solid electrolyte may include Li (7-x) H x La 3 Zr 2 O 12 (0≤x<6.5).
[0091] The surface of the solid electrolyte may include Li (6.75-x) H x La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 (where 0.1≤x<6.75), and its interior may include Li (7-x) H x La 3 Zr 2 O 12 (where 0≤x<6.5). In this case, in the solid electrolyte, the portion of the inorganic lithium ion conductive film on which the porous layer is not formed may include Li 6.75 La 2.9 Ga0.1 Nb 0.25 Zr 1.75 O 12 .
[0092] In the inorganic lithium ion conductive film, the grains of the inorganic lithium ion conductor may have a polyhedral shape. In the case of the grains having a polyhedral shape, the contact area between adjacent grains may be increased, thereby increasing ion conductivity, and the possibility of contact between the active material and the crystal plane effective for the charge transfer reaction is increased, thereby increasing the kinetics of the electrochemical reaction.
[0093] A secondary battery according to another embodiment includes a positive electrode, a negative electrode, and a solid electrolyte interposed between the positive electrode and the negative electrode.
[0094] Reference Figure 3 , a secondary battery according to an embodiment will be described in more detail.
[0095] In the secondary battery 28 , the cathode 27 is located on the cathode current collector 26 , and the solid electrolyte 20 is located on the cathode 27 . Figure 3 The solid electrolyte 20 shown in FIG. 1 includes an inorganic lithium ion conductive membrane 21 and a porous layer 24 thereon. The porous layer 24 of the solid electrolyte 20 is arranged adjacent to the negative electrode 29. The negative electrode current collector 30 is provided (eg, laminated) on the negative electrode 29.
[0096] In the porous layer 24, the first porous layer 23 is located on the surface of the solid electrolyte 20, and the second porous layer 22 having a pore size smaller than the pore size of the first porous layer 23 is located inside the solid electrolyte 20. An electrolyte may be disposed between the positive electrode 27 and the solid electrolyte 20. The electrolyte may include at least one of an ionic liquid, a lithium salt, an organic solvent, or a polymer ionic liquid. The electrolyte may be impregnated in the positive electrode 27.
[0097] The ionic liquid is an ionic material in a molten state at room temperature (25° C.), and may be any material including cations and anions without limitation. Examples of the ionic liquid may include at least one compound including at least one cation and at least one anion. The at least one cation may include at least one of the following: ammonium, pyrrole, , pyridine , pyrimidine Imidazole , piperidine Pyrazole , Azoles Pyridazine , , sulfonium, or triazole The at least one anion may include at least one of the following: BF4 -PF 6 -、AsF 6 -、SbF 6 -、AlCl 4 -、HSO 4 -、ClO 4 -、CH 3 SO 3 -、CF 3 CO 2 -、Cl-、Br-、I-、SO 4 2 -、CF 3 SO 3 -、(FSO 2 ) 2 N-、(C 2 F 5 SO 2 ) 2 N-、(C 2 F 5 SO 2 )(CF 3 SO 2 )N-, or (CF 3 SO 2 ) 2 N-.
[0098] For example, the ionic liquid may be at least one of the following: [emim]Cl / AlCl 3 (emim is ethylmethylimidazole ),[bmpyr]NTf 2 (bmpyr is butyl methyl pyridine )、[bpy]Br / AlCl 3 (bpy=4,4'-bipyridine), [choline]Cl / CrCl 3 6H 2 O, [emim]OTf / [hmim]I (hmim is hexylmethylimidazole ), [Choline]Cl / HOCH 2 CH 2 OH, [Et 2 MeN(CH 2 CH 2 OMe)]BF 4 (Et is ethyl, Me is methyl, Pr is propyl, Bu is butyl, Ph is phenyl, Oct is octyl, Hex is hexyl), [Bu 3 PCH 2 CH 2 C 8 F 17]OTf (OTf is trifluoromethanesulfonate), [bmim]PF 6 (bmim is butylmethylimidazole )、[bmim]BF 4 、[omim]PF 6 (omim is octylmethylimidazole ), [Oct 3 PC 18 H 37 ]I, [NC(CH 2 ) 3 mim]NTf 2 (mim is methylimidazole ), [Pr 4 N][B(CN) 4 ]、[bmim]NTf 2 、[bmim]Cl、[bmim][Me(OCH 2 CH 2 ) 2 OSO 3 ]、[PhCH 2 mim]OTf, [Me 3 NCH(Me)CH(OH)Ph]NTf 2 、[pmim][(HO) 2 PO 2 ](pmim is propylmethylimidazole )、[(6-Me)bquin]NTf 2 (bquin is butylquinoline ), [bmim] [Cu 2 Cl 3 ]、[C 18 H 37 OCH 2 mim]BF 4 (mim is methylimidazole ), [heim]PF 6 (heim is hexylethylimidazole )、[mim(CH 2 CH 2 O) 2 CH 2 CH 2 mim][NTf 2 ] 2 (mim is methylimidazole ), [obim]PF 6 (obim is octylbutylimidazole ),[oquin]NTf 2 (oquin is octylquinoline ),[hmim][PF 3 (C 2 F 5 ) 3 ]、[C 14 H 29 mim]Br (mim is methylimidazole ), [Me 2 N(C 12 H 25 ) 2 ]NO 3 、[emim]BF 4 、[MeN(CH 2 CH 2 OH) 3 ][MeOSO 3 ]、[Hex 3 PC 14 H 29 ]NTf 2 、[emim][EtOSO 3 ], [choline] [ibuprofenate], [emim] NTf 2 、[emim][(EtO) 2 PO 2 ]、[emim]Cl / CrCl 2 、[Hex 3 PC 14 H 29 ]N(CN) 2 However, the ionic liquid is not limited thereto, and any appropriate ionic liquid may be used therefor.
[0099] Unless otherwise specified, mim is methylimidazole , emim is ethylmethylimidazole , hmim is hexylmethylimidazole , obim is octylbutylimidazole , bmim is butylmethylimidazole , omim is octylmethylimidazole , pmim is propylmethylimidazole , bmpyr is butyl methyl pyridine , bpy is 4,4'-bipyridine, Et is ethyl, Me is methyl, Pr is propyl, Bu is butyl, Ph is phenyl, Oct is octyl, Hex is hexyl, py is pyridine, and obim is octylbutylimidazole , bquin is butylquinoline ,heim is hexylethylimidazole , oquin is octylquinoline , OTf is trifluoromethanesulfonate, and NTf 2 It is bis(trifluoromethanesulfonyl)imide.
[0100] The lithium salt may include at least one of the following: LiSCN, LiN(CN) 2 、LiClO 4 , LiBF 4 、LiAsF 6 、LiPF 6 、LiCF 3 SO 3 、LiC(CF 3 SO 2 ) 3 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 F) 2 、LiSbF 6 、LiPF 3 (CF 2 CF 3 ) 3 、LiPF 3 (CF 3 ) 3 , or LiB(C 2 O 4 ) 2 In addition, the concentration of the lithium salt is about 1M to about 6M, or for example, about 1.5M to about 5M.
[0101] The negative electrode 29 may be a lithium metal negative electrode.
[0102] The solid electrolyte 20 and the negative electrode 29 may be bonded to each other by a method known to those skilled in the art. For example, the solid electrolyte and the negative electrode may be bonded to each other by cold isostatic pressing (CIP). According to another embodiment, the solid electrolyte 20 and the negative electrode 29 may be bonded via molten Li or a polyethylene oxide binder.
[0103] The secondary battery 28 may further include at least one of: a liquid electrolyte, a polymer electrolyte, or a lithium salt.
[0104] The liquid electrolyte may include a lithium salt and an organic solvent.
[0105] The organic solvent may include an aprotic solvent or a protic solvent. The example of the aprotic solvent may include a carbonate-based solvent, an ester-based solvent, an ether-based solvent, or a ketone-based solvent. The protic solvent may include an alcohol-based solvent. The example of the carbonate-based solvent may include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). The example of the ester-based solvent may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decalactone, valerolactone, mevalonolactone, and caprolactone. The example of the ether-based solvent may include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and tetraethylene glycol dimethyl ether (TEGDME). The example of the ketone-based solvent may include cyclohexanone. In addition, the example of the alcohol-based solvent may include ethanol and isopropanol. However, the example of the aprotic solvent is not limited thereto, and any material that can be used as an aprotic solvent in the art may also be used.
[0106] The polymer electrolyte may be any polymer electrolyte suitable for use in secondary batteries.
[0107] A solid sulfide electrolyte may be further disposed between the negative electrode and the solid electrolyte. For example, the solid sulfide electrolyte may be Li 2 SP 2 S 5 -LiX (wherein X is at least one of F, Cl, Br, or I).
[0108] The secondary battery may be configured to provide a charge at 3 mA / cm2 at 1,000 cycles, for example, at 1,700 cycles. 2 ) current density.
[0109] The lifespan of the secondary battery is greater than 1,700 cycles when the secondary battery has a capacity of 80% of an initial capacity.
[0110] The negative electrode may be a lithium metal electrode or a lithium metal alloy electrode. A surface of the solid electrolyte in contact with the negative electrode has a larger pore size than a portion of the solid electrolyte farthest from the negative electrode.
[0111] The secondary battery may be a lithium metal battery including a negative electrode including at least one of lithium metal or a lithium metal alloy.
[0112] In a lithium metal battery including a lithium metal negative electrode, the solid electrolyte according to the embodiment may serve as a protective layer to protect the lithium metal negative electrode. The solid electrolyte according to the embodiment and the lithium metal negative electrode may together constitute a protective negative electrode.
[0113] Hereinafter, a method of preparing a secondary battery according to an embodiment will be described.
[0114] The positive electrode was prepared according to the following method.
[0115] A positive electrode active material, a binder, and a solvent are mixed to prepare a positive electrode active material composition.
[0116] A conductive agent may be further added to the positive electrode active material composition.
[0117] The positive electrode active material composition may be directly coated on a metal current collector and dried to prepare a positive electrode plate. Alternatively, the positive electrode active material composition may be cast on a separate support and then a film separated from the support may be laminated on a metal current collector to prepare a positive electrode plate.
[0118] The binder promotes the bonding of the positive electrode active material with the conductive agent, the current collector, etc. Examples of the binder may include, but are not limited to, at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or a copolymer thereof.
[0119] The conductive agent may be any material that has conductivity and does not cause chemical changes. For example, the conductive agent may be at least one of the following: graphite such as natural graphite and artificial graphite; carbonaceous materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. A combination comprising at least two of the foregoing may also be used.
[0120] The solvent may be N-methylpyrrolidone (NMP), without being limited thereto.
[0121] The amounts of the positive electrode active material, conductive agent, binder, and solvent can be determined by those skilled in the art without undue experimentation. Depending on the purpose and structure of the lithium battery, at least one of the conductive agent, binder, or solvent may not be used.
[0122] The positive electrode active material used to prepare the positive electrode may include at least one of lithium cobalt oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, or lithium manganese oxide, without being limited thereto, and any suitable positive electrode active material may also be used.
[0123] For example, the positive electrode active material may include at least one of the following: Li a A 1-b B' b D 2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b B' b O 2-c D c (where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); LiE 2- b B b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B' c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E c G d O 2(where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NeG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a MnG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 2 G b O 4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); QO 2 ;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (0≤f≤2);Li (3-f) Fe 2 (PO 4 ) 3 (0≤f≤2); or LiFePO 4 .
[0124] In the above formulas, A is nickel (Ni), cobalt (Co), manganese (Mn), or any combination thereof; B' is aluminum (Al), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), iron (Fe), magnesium (Mg), strontium (Sr), vanadium (V), rare earth elements, or any combination thereof; D is oxygen (O), fluorine (F), sulfur (S), phosphorus (P), or any combination thereof; E is cobalt (Co), manganese (Mn), or any combination thereof; F' is fluorine (F), sulfur (S), phosphorus (P), or any combination thereof combination; G is aluminum (Al), chromium (Cr), manganese (Mn), iron (Fe), magnesium (Mg), lanthanum (La), cerium (Ce), strontium (Sr), vanadium (V), or any combination thereof; Q is titanium (Ti), molybdenum (Mo), manganese (Mn), or any combination thereof; I' is chromium (Cr), vanadium (V), iron (Fe), scandium (Sc), yttrium (Y), or any combination thereof; and J is vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), or any combination thereof.
[0125] For example, the positive electrode active material may be at least one of the compounds represented by Formula 1, 2, or 3 below.
[0126] Formula 1
[0127] Li a Ni b Co c Mn d O 2
[0128] In Formula 1, 0.90≤a≤1.8, 0≤b≤0.95, 0≤c≤0.5, and 0≤d≤0.5.
[0129] Formula 2
[0130] Li 2 MnO 3
[0131] Formula 3
[0132] LiMO 2
[0133] In Formula 3, M is Mn, Fe, Co, or Ni.
[0134] The lithium secondary battery may further include at least one of a liquid electrolyte, a solid electrolyte, a gel electrolyte, or a polymer ionic liquid.
[0135] The negative electrode may be a lithium metal negative electrode including at least one of a lithium metal electrode or a lithium metal alloy, or may include a negative electrode active material, wherein the negative electrode active material includes at least one of the following: a carbonaceous material, silicon, silicon oxide, a silicon alloy, a silicon-carbon composite, tin, a tin alloy, a tin-carbon composite, a metal / metalloid capable of alloying with lithium, an alloy thereof, or an oxide thereof.
[0136] As described above, the negative electrode may be at least one of a lithium metal film or a lithium metal alloy film.
[0137] The lithium metal alloy may include Li and a metal / metalloid that can be alloyed with Li. For example, the metal / metalloid that can be alloyed with Li may be Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y' alloy (Y' is at least one of an alkali metal, an alkaline earth metal, an element of Group 13-16, a transition metal, and a rare earth element, excluding Si), and Sn-Y' alloy (Y' is at least one of an alkali metal, an alkaline earth metal, an element of Group 13-16, a transition metal, and a rare earth element, excluding Sn). In this regard, Y' may be at least one of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, or Po.
[0138] A solid electrolyte according to an embodiment is located on the negative electrode.
[0139] The secondary battery may be prepared by housing the positive electrode in a battery case, injecting an electrolyte therein, and placing the positive electrode on one surface of the solid electrolyte having the negative electrode mounted on the other surface thereof.
[0140] The electrolyte may include at least one of a lithium salt, an ionic liquid, a polymer ionic liquid, or an organic solvent. For example, the electrolyte includes a lithium salt and an ionic liquid.
[0141] The secondary battery may be, for example, a lithium secondary battery using a lithium electrode as a negative electrode, a lithium air battery using a lithium electrode as a negative electrode and using oxygen as a positive electrode, a lithium sulfur battery using a lithium electrode as a negative electrode and a positive electrode including sulfur or an active material containing sulfur, and the like.
[0142] The secondary battery according to the embodiment may further include at least one of sodium, magnesium, calcium, or aluminum as a material for forming the negative electrode in addition to lithium.
[0143] A secondary battery including the solid electrolyte according to the embodiment may be, for example, an all-solid-state secondary battery or a lithium-ion secondary battery.
[0144] The surface structure and composition of the solid electrolyte according to the embodiment can be analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), inductively coupled plasma (ICP) analysis, X-ray photoelectron spectroscopy (XPS), etc.
[0145] A method for preparing a solid electrolyte according to another embodiment includes acid-treating an inorganic lithium ion conductive membrane by applying an acid having a concentration greater than or equal to 0.1 M and less than 5 M thereto; and washing the acid-treated product. In particular, the method includes: a first acid treatment, which includes acid-treating the inorganic lithium ion conductive membrane with an acid having a concentration greater than 0.1 molar concentration and less than or equal to about 5 molar concentration to provide a first acid-treated product; and a first washing, which includes washing the first acid-treated product to provide a washed first acid-treated product, forming the solid electrolyte.
[0146] The acid treatment may be performed by immersing a portion of the inorganic lithium ion conductive membrane in the acid, or placing a mask on the inorganic lithium ion conductive membrane and applying the acid only on a portion of the inorganic lithium ion conductive membrane.
[0147] The acid treatment time may vary depending on the concentration of the acid and may be, for example, about 0.1 hour to about 2 hours. In addition, the acid treatment is performed under dry air conditions (eg, 0% relative humidity) to minimize the reaction between the surface of the solid electrolyte and moisture in the air.
[0148] The pore size, porosity, and thickness of the porous layer of the solid electrolyte may vary according to the concentration of the acid during the acid treatment and the acid treatment time.
[0149] In the solid electrolyte (e.g. Li 7 La 3 Zr 2 O 12 In a part of the acid-treated surface of the acid-treated layer (layer) or the entire acid-treated surface, lithium ions are replaced by protons and thus lithium carbonate is removed from the surface, as shown in the following Reaction Scheme 1.
[0150] Reaction Scheme 1
[0151] Li 7 La 3 Zr 2 O 12 +Li 2 CO 3 +2HCl+xH2 O→Li (7-x) H x La 3 Z r2 O 12 +xLiOH+2LiCl+CO 2
[0152] In reaction scheme 1, 0 <x≤7。
[0153] When the part of the solid electrolyte replaced by protons contacts an acid for a predetermined period of time, dissolution of the solid electrolyte may occur by decomposition of the solid electrolyte. In this dissolution, grains with a smaller size and a relatively high energy state selectively dissolve from the grain boundaries at the surface of the electrolyte layer. Since holes are formed in the position where the grains with a small size are completely dissolved, a porous layer is formed on the surface of the solid electrolyte. The thickness, porosity, and pore size of the porous layer located on the surface of the solid electrolyte and inside the solid electrolyte can be adjusted by changing the acid treatment conditions such as the concentration of the acid and the acid treatment time.
[0154] The washing can be performed by using, for example, ethanol.
[0155] The inorganic lithium ion conductive membrane may be prepared by combining an inorganic lithium ion conductor and a lithium compound to prepare a mixture, and heat-treating the mixture.
[0156] An inorganic lithium ion conductor is prepared by a solid phase method or a liquid phase method using a precursor for forming an inorganic lithium ion conductor. The inorganic lithium ion conductor and a lithium compound are combined to prepare a mixture, and the mixture is processed into a form of a pellet, a sheet, or a film. The product in the form of a pellet or a sheet is heat treated. The heat treatment temperature may vary depending on the type and amount of the inorganic lithium ion conductor and the lithium compound, and may be, for example, about 25° C. to about 80° C.
[0157] The heat-treated product is polished to remove impurities remaining on the surface or generated during the heat treatment. The polishing can be performed by using an automatic polishing machine.
[0158] The lithium compound is a material capable of supplying lithium to the inorganic lithium ion conductor. Examples of the lithium compound may include at least one of lithium carbonate, lithium hydroxide, or lithium oxide. The amount of the lithium compound is in the range of about 0.1 parts by weight to about 10 parts by weight, for example, about 1 part by weight to about 8 parts by weight, or for example, about 3 parts by weight to about 5 parts by weight, based on the total weight of 100 parts by weight of the inorganic lithium ion conductor and the lithium compound. When the amount of the lithium compound is within the above range, a solid electrolyte including a porous layer having a desired pore size and porosity can be obtained. By adding an excess of the lithium compound during the preparation of the solid electrolyte, a porous layer having a predetermined thickness can be formed during the acid treatment with a strong acid without structural collapse.
[0159] The method may further include: a second acid treatment, which includes acid-treating the washed first acid-treated product with an acid having a concentration greater than 0.1 molar concentration and less than or equal to 5 molar concentration to provide a second acid-treated product; and a second washing, which includes washing the second acid-treated product. For example, the second acid treatment performed by applying an acid having a concentration greater than 0.1M and less than 5M thereto and the second washing process of washing the product obtained by the second acid treatment may be repeatedly performed.
[0160] The concentration of the acid used in the second acid treatment is less than the concentration of the acid used in the previous (eg, first) acid treatment.
[0161] The washed product is dried, for example, at about 25°C to about 60°C.
[0162] The acid may include at least one of: HCl, H 3 PO 4 , HNO 3 , H 2 SO 4 , or acetic acid, but not limited thereto.
[0163] A method for preparing a solid electrolyte according to another embodiment includes: forming a multilayer film on the surface of an inorganic lithium ion conductive film, the forming including: coating a first composition including a pore former and a lithium ion conductor on the surface of the inorganic lithium ion conductive film, and drying the first composition, coating a second composition including a pore former and a lithium ion conductor on the dried first composition, and drying the second composition to form a multilayer film; and heat-treating the multilayer film. The amount of the pore former in the first composition may be different from the amount of the pore former in the second composition.
[0164] The pore former may be any material capable of forming pores in the multilayer. Examples of the pore former may include at least one of dibutyl phthalate, dimethyl phthalate, diethyl phthalate, dioctyl sebacate, and dioctyl adipate.
[0165] Hereinafter, one or more embodiments will be described in detail with reference to the following examples and comparative examples. However, these examples and comparative examples are not intended to limit the purpose and scope of one or more embodiments.
[0166] Example
[0167] Preparation Example 1: Preparation of LLZO film
[0168] Li via solid phase method 7 La 3 Zr 2 O 12 (LLZO) powder. 7 La 3 Zr 2 O 12 (LLZO) powder was prepared in the same manner as described in Example 1 of U.S. Patent Application Publication No. 2016 / 0149260 (which is incorporated herein by reference in its entirety) except that Li 2 CO 3 、LiOH、La 2 O 3 , and ZrO 2 as oxide precursors.
[0169] Li 7 La 3 Zr 2 O 12 (LLZO) powder and lithium carbonate (Li 2 CO 3 ) is uniaxially pressed at a pressure of about 10 MPa to form a layer. The amount of lithium carbonate is 5.5 parts by weight, based on Li 7 La 3 Zr 2 O 12 (LLZO) powder and lithium carbonate (Li 2 CO 3 ) of the total weight of 100 parts by weight.
[0170] Next, the layer is coated with a matrix powder (Li 7 La 3 Zr 2 O 12) and heat-treated at 1300° C. for 4 hours. The surface of the heat-treated layer was polished using an automatic polisher to prepare an LLZO film (thickness: about 300 μm).
[0171] Preparation Example 2: Preparation of LLZO film
[0172] The LLZO film was prepared in the same manner as in Preparation Example 1, except that Li 6.4 La 3 Zr 1.7 W 0.3 O 12 (W-doped LLZO) powder instead of Li 7 La 3 Zr 2 O 12 (LLZO) powder.
[0173] Preparation Example 3: Preparation of LLZO film
[0174] The LLZO film was prepared in the same manner as in Preparation Example 1, except that Li 6.5 La 3 Zr 1.5 Ta 0.3 O 12 (Ta-doped LLZO) powder instead of Li 7 La 3 Zr 2 O 12 (LLZO) powder. Preparation Examples 4 and 4a: Preparation of LLZO films
[0175] The LLZO film was prepared in the same manner as in Preparation Example 1, except that lithium carbonate was used in an amount of 0.1 parts by weight and 10 parts by weight based on Li 7 La 3 Zr 2 O 12 (LLZO) powder and lithium carbonate (Li 2 CO 3 ) of the total weight of 100 parts by weight.
[0176] Preparation Example 5: Preparation of LLZO film
[0177] The LLZO film was prepared in the same manner as in Preparation Example 1, except that during the uniaxial pressing process, lithium hydroxide was used instead of lithium carbonate, and the Li 7 La 3 Zr 2 O 12 Uniaxial pressing of (LLZO) powder and lithium hydroxide.
[0178] Preparation Comparative Example 1: Preparation of LLZO Film
[0179] The LLZO film was prepared in the same manner as in Preparation Example 1, except that: 7 La 3 Zr 2 O 12 During the uniaxial pressing process of (LLZO) powder, no Li 7 La 3 Zr 2 O 12 (LLZO) powder added with lithium carbonate (Li 2 CO 3 ).
[0180] Preparation Comparative Example 1-1
[0181] The LLZO film was prepared according to the following method described in Energy Environ. Sci., 2017, 1568-1575, page 1573, which is incorporated herein by reference in its entirety.
[0182] LLZO powder and poly(methyl methacrylate) (PMMA) as a pore-forming agent were added to a mixed solvent of toluene and isopropanol, and the mixture was mixed for about 1 hour to prepare a porous layer slurry. Fish oil, polyvinyl butyral, and butyl benzyl phthalate (BBP) were added to the porous layer slurry as a binder and a dispersant. The porous layer slurry was coated on a Li-100 surface by screen printing. 7 La 3 Zr 2 O 12 The porous LLZO film was prepared by heat treatment at about 1100° C. for 2 hours.
[0183] Example 1: Preparation of solid electrolyte
[0184] A mask is placed on the LLZO film prepared according to Preparation Example 1, and the LLZO film is subjected to a first acid treatment for 10 minutes as follows: a 1M HCl aqueous solution is dropped on the exposed portion of the LLZO film. The product obtained by the first acid treatment is washed with ethanol and dried to form a porous layer on the surface of the LLZO film. The acid treatment and washing are repeated twice in sequence to perform a second acid treatment and a third acid treatment, thereby increasing the porosity and thickness of the porous layer. The concentration of the acid and the acid treatment time of the second and third acid treatments are the same as those of the first acid treatment. The acid treatment is carried out under dry air conditions (e.g., 0% relative humidity) to minimize the reaction between the surface of the solid electrolyte and the moisture in the air. The resulting product obtained after washing is dried at about 25°C to prepare a solid electrolyte.
[0185] Example 2 and Comparative Example 1: Preparation of solid electrolyte
[0186] A solid electrolyte was prepared in the same manner as described in Example 1, except that the acid concentration and the acid treatment time were each changed for the first, second, and third acid treatments as shown in Table 1 below.
[0187] Table 1
[0188]
[0189] Example 3: Preparation of solid electrolyte
[0190] The solid electrolyte was prepared in the same manner as described in Example 1, except that the concentration of the acid used in the first to third acid treatments and the acid treatment time were changed as shown in the following Table 2. When the acid treatment was performed while gradually decreasing the concentration of the acid as shown in Table 2, the particle connection in the porous layer was well maintained.
[0191] Table 2
[0192]
[0193] Example 5: Preparation of solid electrolyte
[0194] A solid electrolyte was prepared in the same manner as in Example 1, except that both surfaces of the LLZO film were acid-treated.
[0195] The acid treatment performed on both surfaces of the LLZO film includes immersing the LLZO film in a 1M HCl aqueous solution for about 10 minutes, washing the film using ethanol, and drying the resultant.
[0196] Examples 6 and 7: Preparation of solid electrolyte
[0197] Solid electrolytes were prepared in the same manner as in Example 1, except that the LLZO membranes of Preparation Example 2 and Preparation Example 3 were used instead of the LLZO membrane of Preparation Example 1, respectively.
[0198] Example 7a: Preparation of solid electrolyte
[0199] A solid electrolyte was prepared in the same manner as in Example 1, except that the LLZO membrane of Preparation Example 5 was used instead of the LLZO membrane of Preparation Example 1.
[0200] Comparative Example 2: Preparation of solid electrolyte
[0201] A solid electrolyte was prepared in the same manner as in Example 1, except that the LLZO film prepared according to Comparative Preparation Example 1 was used instead of the LLZO film prepared according to Preparation Example 1.
[0202] Example 8: Preparation of lithium secondary battery
[0203] First, a positive electrode was prepared according to the following method.
[0204] LiNi 0.33 Co 0.33 Mn 0.33 O 2 (NCM), polyvinylidene fluoride (PVDF), Super P as a conductive agent and N-methylpyrrolidone are mixed to obtain a positive electrode active material layer forming composition. In the positive electrode active material layer forming composition, the weight ratio of NCM to Super P to PVDF is 97:1.5:1.5. When the amount of NCM is 97 grams (g), the amount of N-methylpyrrolidone is about 137g.
[0205] The cathode active material layer-forming composition was coated on an Al foil (thickness: about 15 μm) and dried at 25° C., and the dried resultant was further dried at about 110° C. in a vacuum to prepare a cathode.
[0206] A lithium metal anode (thickness: about 20 μm) was disposed on a current collector (Cu foil), and the lithium metal anode and the solid electrolyte were combined by applying a pressure of about 250 MPa by using a cold isostatic pressing (CIP) method.
[0207] The positive electrode prepared as described above was placed in a stainless battery case and a positive electrode electrolyte was added thereto. Then, the positive electrode was placed on one surface of the solid electrolyte prepared according to Example 1, and the other surface of the solid electrolyte was equipped with the lithium metal negative electrode (thickness: 20 μm) to prepare a lithium secondary battery (refer to Figure 3 ).
[0208] The positive electrode electrolyte is prepared by mixing LiFSI as a lithium salt and bis(fluorosulfonyl)imide N-methyl-N-propylpyrrolidine as an ionic liquid having the structure shown below. (Pyr13FSI, Pyr 13 + cation structure) mixed with 2M LiFSI ionic liquid.
[0209]
[0210] Examples 9-11: Preparation of lithium secondary batteries
[0211] A lithium secondary battery was prepared in the same manner as in Example 8, except that the solid electrolyte prepared according to Examples 6, 7, and 7a was used instead of the solid electrolyte of Example 1.
[0212] Comparative Example 3: Preparation of lithium secondary battery
[0213] A lithium secondary battery was prepared in the same manner as in Example 8, except that the LLZO film prepared according to Preparation Example 1 was used instead of the solid electrolyte of Example 1.
[0214] Comparative Example 4: Preparation of lithium secondary battery
[0215] A lithium secondary battery was prepared in the same manner as in Example 8, except that the solid electrolyte of Example 1 was replaced by a solid electrolyte prepared according to Preparation Comparative Example 1-1 as described in reference to “Garnet solid-state electrolyte preparation”, Energy Environ. Sci., 2017, 1568-1575, page 1573 (all of which are incorporated herein by reference).
[0216] Comparative Example 5: Preparation of lithium secondary battery
[0217] A lithium secondary battery was prepared in the same manner as in Example 8, except that the solid electrolyte of Comparative Example 2 was used instead of the solid electrolyte of Example 1.
[0218] Comparative Examples 6 and 7: Preparation of lithium secondary batteries
[0219] A lithium secondary battery was prepared in the same manner as in Example 8, except that the solid electrolyte prepared according to Comparative Preparation Examples 1-2 and 1-4 was used instead of the solid electrolyte of Example 1.
[0220] A lithium secondary battery was prepared in the same manner as in Example 8, except that poly(vinylidene fluoride) (PVDF) was used as a separator instead of the LLZO solid electrolyte and Li metal was bonded thereto without performing the CIP method.
[0221] Evaluation Example 1: Scanning Electron Microscopy (SEM)
[0222] The cross sections of the solid electrolytes prepared according to Example 1 and Comparative Preparation Example 1-1 were observed by using a scanning electron microscope (SEM). SU8030 available from Hitachi, Ltd. was used as the SEM. The SEM image of the solid electrolyte of Example 1 is shown in Figure 4A and 4B middle. Figure 4B It is drawn by dotted lines Figure 4A In addition, the SEM image of the LLZO film prepared according to the comparative example 1-1 is shown in Figure 4C middle.
[0223] Reference Figure 4A A second porous layer 42 having a thickness of about 10 μm and a pore size of 5 μm or less is formed on the LLZO film 41, and a first porous layer 43 having a thickness of about 20 μm and a pore size greater than 20 μm is formed thereon. The total thickness of the second porous layer 42 and the first porous layer 43 is about 30 μm. In addition, referring to Figure 4B , small grains are selectively dissolved by acid treatment with a strong acid to form pores, and surfaces of remaining grains are partially dissolved so that the remaining grains have a polyhedral shape deviating from a circular shape.
[0224] Reference Figure 4C , it can be confirmed that, when the porous layer is formed by screen printing, the same pore size is distributed throughout the porous layer and there are no open pores on the surface.
[0225] The pore size distribution and mechanical strength (ring-on-ring test) of the solid electrolytes prepared according to Examples 6 and 7 and Comparative Example 2 were measured. The pore size distribution was measured by using an Autopore IV 9520 available from Micromeritics Instrument Corp., and the mechanical strength was evaluated according to the ring-on-ring test by using an MTS 10D Load Frame available from Sintechcorporation with a 0.75-inch diameter support ring and a 0.25-inch diameter load ring.
[0226] The pore size distribution of the solid electrolytes prepared according to Examples 6 and 7 is shown in Figure 5A and the pore size distribution of the solid electrolyte prepared according to Comparative Example 2 is shown in Figure 5B middle.
[0227] The evaluation results of the mechanical strength of the solid electrolytes prepared according to Example 6 and Comparative Example 2 are shown in Table 3.
[0228] Table 3
[0229]
[0230]
[0231] like Figure 5A and 5B As shown in, it is confirmed that, compared with the solid electrolyte prepared according to Comparative Example 2, the solid electrolyte prepared according to Example 6 has a wide pore size distribution (200 μm-0.5 μm) by surface treatment using a 1M HCl aqueous solution. The solid electrolyte prepared according to Example 6 has a structure in which the pore size gradually decreases from the surface of the solid electrolyte to the inside thereof. In addition, the solid electrolyte of Example 6 has a mechanical strength similar to that of the solid electrolyte of Comparative Example 2 that does not include a porous layer. In addition, the mechanical strength of the solid electrolyte of Example 7 is similar to that of the solid electrolyte of Example 6.
[0232] Evaluation Example 2: XRD Characteristics
[0233] X-ray diffraction (XRD) analysis was performed on the LLZO film of Preparation Example 1 and the solid electrolyte of Example 1. The XRD analysis was performed by using D8 Advance available from Bruker.
[0234] The XRD analysis results are shown in Fig. 6A and 6B middle. Figure 6B It is marked with a circle Fig. 6A In addition, the LLZO film of Preparation Example 1 and the solid electrolyte of Example 1 were subjected to XRD analysis, and their space groups, lattice constants a, and average grain sizes were measured and shown in Tables 4, Fig. 6A ,and Figure 6B middle.
[0235] Table 4
[0236]
[0237] Reference Fig. 6A and 6BAs well as Table 4, it is confirmed that the crystallographic characteristics of the solid electrolyte prepared according to Example 1 have changed due to the replacement of lithium ions by protons compared to the LLZO film prepared according to Preparation Example 1. As a result of XRD analysis, the acid-treated solid electrolyte has an increased crystallinity and an increased lattice constant due to proton substitution and an increased average grain size due to a decrease in the number of small grains. This is consistent with the analysis results of the SEM image.
[0238] Evaluation Example 3: Impedance Characteristics
[0239] The impedance of the lithium secondary batteries of Example 8 and Comparative Example 3 was measured. The impedance was measured by using an impedance analyzer (Solartron 1260A impedance / gain-phase analyzer) at 60° C. for about 10 min in an open circuit state before life evaluation according to a 2-probe method. 6 The frequency range is from megahertz (MHz) to about 0.1 MHz while applying an AC voltage bias of 10 millivolts (mV).
[0240] The impedance results are shown in Fig. 7A and 7B middle. Fig. 7A and 7B is a graph illustrating impedance characteristics of lithium secondary batteries prepared according to Example 8 and Comparative Example 3.
[0241] Reference Fig. 7A and 7B The total interfacial resistance of the lithium secondary battery of Example 8 is reduced compared to the total interfacial resistance of the lithium secondary battery of Comparative Example 3. The interfacial resistance is reduced due to the following reasons: the surface area is increased due to the formation of a porous layer on the solid electrolyte, and the surface impurities such as lithium carbonate (LiCO) are increased due to the increase of the interfacial active area between the solid electrolyte and the lithium metal electrode. 2 CO 3 ) is removed.
[0242] Evaluation Example 4: Charge / Discharge Characteristics
[0243] By the following conditions at 0.64mA / cm 2 The charge / discharge characteristics of the lithium secondary batteries prepared according to Example 8 and Comparative Examples 3 and 4 were evaluated by a constant current method at a current density of .
[0244] Each lithium secondary battery was charged at 60°C in a constant current mode at 0.3 mA / cm 2 The battery was charged at a current of 0.15 mA / cm2 until the voltage reached 4.0 V (vs. Li) and the battery was charged at 0.15 mA / cm2 while maintaining the voltage of 4.0 V in a constant voltage mode. 2 Then, the lithium secondary battery was charged at 0.3 mA / cm 2The battery was discharged at a constant current until the voltage reached 2.8 V (vs. Li) (1st cycle, formation cycle).
[0245] At 60°C and 0.5 mA / cm 2 and 0.64mA / cm 2 The charging and discharging of the lithium secondary battery was repeated 1800 times at a current of .
[0246] Evaluation results of the charge / discharge characteristics of the lithium secondary batteries prepared according to Example 8 and Comparative Examples 3 and 4 are shown in Figures 8A-8C middle.
[0247] like Figure 8B and 8C As shown in FIG. 1 , in the lithium secondary batteries according to Comparative Examples 3 and 4, when the battery is charged at a current density of 0.64 mA / cm 2 In the case of constant current charging and discharging (galvanostatic method), voltage noise due to Li shortage was observed during the 3rd and 4th charging runs.
[0248] In contrast, in the lithium secondary battery prepared according to Example 8, a high capacity retention rate and no short circuit were observed during charging and discharging at least until the 10th cycle. Without being limited by any theory, it is believed that this is because the surface porous layer formed by the acid treatment forms a stable interface with the lithium metal, and thus prevents Li plating and stress concentration at the grain boundary, thereby inhibiting Li from penetrating the solid electrolyte.
[0249] Evaluation Example 5: Charge / Discharge Characteristics
[0250] 1) Example 8 and Comparative Example 8
[0251] In order to confirm the life characteristics of the lithium secondary batteries prepared according to Example 8 and Comparative Example 8 at a high current density, a current density of 2 mAh / cm 2 The capacity of each unit cell at 3mA / cm 2 The charging and discharging test results of the lithium secondary battery of Example 8 are shown in Fig.9A and 9B The charging and discharging test results of the lithium secondary battery of Comparative Example 8 are shown in Fig. 9C middle.
[0252] Fig.9A A graph illustrating electrode potential of a lithium secondary battery prepared according to Example 8; and Fig. 9B A graph illustrating electrode potential relative to capacity of a lithium secondary battery according to Example 8. Fig. 9C Graph illustrating electrode potential of a lithium secondary battery prepared according to Comparative Example 8 with respect to the number of cycles.
[0253] Each lithium secondary battery was charged at 60°C in a constant current mode at 0.3 mA / cm 2 The battery was charged at a current of 0.15 mA / cm2 until the voltage reached 4.0 V (vs. Li) and the battery was charged at 0.15 mA / cm2 while maintaining the voltage of 4.0 V in a constant voltage mode. 2 Then, the lithium secondary battery was charged at 0.3 mA / cm 2 The battery was discharged at a constant current until the voltage reached 2.8 V (vs. Li) (1st cycle, formation cycle).
[0254] At 60°C, the 2 The charging and discharging of the lithium secondary battery was repeated (1800 times) at a current of .
[0255] like Fig.9A and 9B As shown in , it can be confirmed that the lithium secondary battery prepared according to Example 8 can be operated for 1000 cycles without short circuit and rapid decrease in capacity. It can also be confirmed that the lithium secondary battery of Example 8 has excellent life characteristics by using a solid electrolyte having a porous layer formed by acid treatment. In contrast, Fig. 9C As shown in , the life characteristics of the lithium secondary battery of Comparative Example 8 using an ionic liquid electrolyte and a separator deteriorate due to a continuous shortage of Li caused by a side reaction between the liquid electrolyte and lithium metal. Fig. 9C As shown in , the lithium secondary battery of Comparative Example 8 has a capacity retention rate of 80% or less within 70 cycles.
[0256] 2) Examples 8 and 11 and Comparative Examples 6 and 7
[0257] In order to confirm the change in electrode potential relative to capacity of the lithium secondary batteries prepared according to Examples 8 and 11 and Comparative Examples 6 and 7, a 2 mAh / cm 2 The capacity of each unit cell at 3mA / cm 2 The charging and discharging test results of the lithium secondary batteries of Examples 8 and 11 are shown in Fig.13A and 13B The charging and discharging test results of the lithium secondary batteries of Comparative Examples 6 and 7 are shown in Fig.14A and 14B middle.
[0258] Each lithium secondary battery was charged at 60°C in a constant current mode at 0.3 mA / cm 2 The battery was charged at a current of 0.15 mA / cm2 until the voltage reached 4.0 V (vs. Li) and the battery was charged at 0.15 mA / cm2 while maintaining the voltage of 4.0 V in a constant voltage mode.2 Then, the lithium secondary battery was charged at 0.3 mA / cm 2 The battery was discharged at a constant current until the voltage reached 2.8 V (vs. Li) (1st cycle, formation cycle).
[0259] At 60°C, the 2 , 0.5mA / cm 2 and 1.6mA / cm 2 The charging and discharging of the lithium secondary battery was repeated 1800 times at a current of .
[0260] Based on the results, it can be confirmed that the lithium secondary batteries prepared according to Examples 8 and 11 have better electrode potential characteristics than the lithium secondary batteries prepared according to Comparative Examples 6 and 7 due to the use of a solid electrolyte having a porous layer formed by acid treatment. Without being limited by any theory, it is believed that the excellent life characteristics of the lithium secondary batteries of Examples 8 and 11 can be obtained as follows: in the lithium secondary battery of Example 8, the porous layer having a thickness of about 30 μm improves the effect of suppressing lithium penetration, and in the lithium secondary battery of Example 11, pores are effectively formed by maintaining the connection state of the acid-treated particles through the expansion of the grain boundaries.
[0261] Evaluation Example 6: X-ray Photoelectron Spectroscopy (XPS) Analysis
[0262] XPS analysis was performed on the LLZO film prepared according to Preparation Example 1 and the solid electrolyte prepared according to Example 1. The XPS analysis was performed using Quantum 2000 (available from Physical Electronics, Inc., accelerating voltage: 0.5 kiloelectron volts (keV)-15 keV, 300 watts (W), energy resolution: about 1.0 eV, and sputtering rate: 0.1 nanometers / minute (nm / min)).
[0263] The XPS analysis results are shown in Figures 10A-10F middle. Figures 10A-10C are graphs respectively illustrating the Li 1s, C 1s, and O 1s XPS analysis results of the LLZO film prepared according to Preparation Example 1, and Figures 10D-10F Graphs respectively illustrate Li 1s, C 1s, and O 1s XPS analysis results of the solid electrolyte prepared according to Example 1.
[0264] Reference Figures 10A-10F As a result, it can be confirmed that by acid treatment of the surface of the solid electrolyte, Li 2 CO 3can also be decomposed and removed. As a result of XPS depth analysis of the surface of the solid electrolyte by Ar sputtering, it was confirmed that the amount of Li 2 CO 3 significantly decreased in the acid-treated solid electrolyte all the way to beneath the surface. Without being bound by any theory, since Li 2 CO 3 is an inert material with low electronic conductivity and low ionic conductivity, the rate characteristics of the lithium secondary battery deteriorate due to an increase in the resistance of the charge transfer reaction at the interfaces between the solid electrolyte and the positive electrode and the negative electrode in the presence of Li 2 CO 3 . In addition, Li 2 CO 3 can be formed into lithium carbide (Li x C: 0 < x < 1) during charge / discharge through a reductive decomposition reaction to grow Li dendrites, resulting in a short circuit. Therefore, by using a solid electrolyte from which Li 2 CO 3 has been removed by acid treatment, the rate characteristics and life characteristics of the lithium secondary battery can be improved.
[0265] Evaluation Example 7: Aging Test
[0266] After exposing the solid electrolytes used in the lithium secondary batteries according to Example 8 and Comparative Example 3 to air for about 18 hours, Li-LLZO-Li symmetric cell batteries were prepared and their impedances were measured. The resistance was measured using an impedance analyzer (Solartron 1260A impedance / gain-phase analyzer) according to the two-probe method at 60 °C while applying an AC voltage bias of 10 mV in a frequency range of about 10 6 MHz - about 0.1 MHz.
[0267] The impedance results of the lithium secondary batteries of Comparative Example 3 and Example 8 are shown in Fig.11A and 11B respectively.
[0268] Referring to the results, compared with Comparative Example 3, the impedance of the solid electrolyte of Example 8 decreased after exposure to oxygen. Therefore, it was confirmed that the stability in air was improved because, on the surface of the solid electrolyte, the formation of lithium carbonate was suppressed due to the replacement of lithium ions by protons.
[0269] Evaluation Example 8: Laser-Induced Breakdown Spectroscopy (LIBS)
[0270] The solid electrolyte prepared according to Example 1 and the LLZO film prepared according to Preparation Example 1 were analyzed by LIBS. LIBS was performed using J200 available from Applied Spectra and the analysis results are shown in Fig. 12A and 12B middle.
[0271] Referring to the results, it was confirmed that the surface of the solid electrolyte of Example 1 was partially substituted with protons by the acid treatment, and the amount of protons decreased in the inward direction toward the inside of the bulk material.
[0272] Since the solid electrolyte according to the embodiment has an increased contact area with the electrode, the interface resistance is reduced. In addition, since the penetration of lithium at the grain boundary of the solid electrolyte is suppressed, short circuits can be reduced. By using the solid electrolyte, a secondary battery with excellent life characteristics can be prepared.
[0273] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for limiting purposes. Descriptions of features or aspects within each embodiment should be considered as available for other similar features or aspects in other embodiments.
[0274] Although one or more embodiments have been described with reference to the drawings, it will be understood by those of ordinary skill in the art that various changes in form and details may be made therein without departing from the spirit and scope as defined by the following claims.
Claims
1. A solid electrolyte comprising: Inorganic lithium ion conducting membrane; and a porous layer on a surface of the inorganic lithium ion conductive membrane, wherein the porous layer comprises a first porous layer and a second porous layer, and the second porous layer is disposed between the inorganic lithium ion conductive membrane and the first porous layer, and wherein the first porous layer has a pore size that is larger than a pore size of the second porous layer, the pore size being determined based on a cross-sectional scanning electron microscopy image, The first porous layer is directly disposed on the second porous layer, The porous layer has an inner surface facing the inorganic lithium ion conductive membrane and an opposite outer surface, and the amount of protons on the outer surface of the porous layer is greater than the amount of protons inside the porous layer, wherein the first porous layer comprises a first inorganic lithium ion conductor substituted with 2% to 100% protons, and the second porous layer comprises a second inorganic lithium ion conductor substituted with 0.01% to 20% protons, based on the total number of protons and lithium ions, The porous layer is a product obtained by: acid-treating the inorganic lithium ion conductive membrane with an acid having a concentration greater than or equal to 0.1 molar concentration and less than or equal to 5 molar concentration, The inorganic lithium ion conductive membrane comprises at least one of a compound of Formula 1 and a compound of Formula 1a: Formula 1 Li 7-x M 1 x La 3-a M 2 a Zr 2-b M 3 b O 12 and Formula 1a <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 7-x <h2 style=";text-align:left;direction:ltr"> No<h2 style=";text-align:left;direction:ltr"> 3-a <h2 style=";text-align:left;direction:ltr"> M<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 2-b <h2 style=";text-align:left;direction:ltr"> M<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> , Among them, in formula 1, M 1 including at least one of gallium or aluminum, 0 <x<3, In formula 1a, 0≤x<3, In Formulas 1 and 1a, M 2 comprising at least one of: calcium, strontium, cesium or barium, M 3 comprises at least one of: aluminum, tungsten, niobium or tantalum, and 0≤a≤3, and 0≤b<2. 2 . The solid electrolyte according to claim 1 , wherein the porosity of the first porous layer is greater than the porosity of the second porous layer.
3. A solid electrolyte as described in claim 1, wherein the pore size of the porous layer increases in the thickness direction of the solid electrolyte, the pore size is determined based on a cross-sectional scanning electron microscopy image, and the thickness direction refers to the direction from the inorganic lithium ion conductive membrane to the opposite surface of the solid electrolyte.
4. The solid electrolyte of claim 3, wherein the pore size of the porous layer increases in a direction from the inorganic lithium ion conductive membrane to the outer surface of the porous layer, the pore size being determined based on a cross-sectional scanning electron microscopy image.
5. The solid electrolyte of claim 1, wherein the porous layer has an overall thickness and density that is impermeable to liquids. 6 . The solid electrolyte according to claim 1 , wherein the porous layer of the solid electrolyte has a thickness of 5% to 95% of the total thickness of the solid electrolyte.
7. The solid electrolyte of claim 1, wherein the pores in the porous layer have an average pore size of 0.1 micrometers to 1000 micrometers, the pore size being determined based on a cross-sectional scanning electron microscopy image.
8. The solid electrolyte of claim 1, wherein the pores in the first porous layer have an average pore size of 10 microns to 500 microns, and The pores in the second porous layer have an average pore size of 0.1 micrometer to 10 micrometers, The pore sizes were determined based on cross-sectional scanning electron microscopy images. 9 . The solid electrolyte according to claim 1 , wherein at least a portion of the solid electrolyte comprises an inorganic lithium ion conductor including lithium ions, and a portion of the lithium ions are substituted with protons. 10 . The solid electrolyte according to claim 9 , wherein the amount of protons in the porous layer is 0.01 mol % to 50 mol % based on the total number of protons and lithium ions.
11. The solid electrolyte of claim 1, wherein the acid has a concentration of 0.5 molar to 4.5 molar.
12. The solid electrolyte of claim 1, wherein the lattice constant of the porous layer measured by X-ray diffraction is 0.005 angstroms to 0.1 angstroms greater than the lattice constant of the remaining region of the solid electrolyte excluding the porous layer, and an average grain size of the porous layer is two or more times larger than an average grain size of a remaining region of the solid electrolyte excluding the porous layer, The grain size was measured by X-ray diffraction analysis.
13. The solid electrolyte of claim 1, wherein the inorganic lithium ion conducting membrane comprises at least one of the following: Li7La3Zr2O 12 , Li 6.4 Ln3Z 1.7 W 0.3 O 12 , Li 6.5 Ln3Z 1.5 Ta 0.3 O 12 、Li7La3Zr 1.7 W 0.3 O 12 , Li 4.9 La 2.5 Ca 0.5 Zr 1.7 Nb 0.3 O 12 , Li 4.9 Ga 2.1 Ln3Z 1.7 W 0.3 O 12 、Li7La3Zr 1.5 W 0.5 O 12 、Li7La 2.75 Ca 0.25 Zr 1.75 Nb 0.25 O 12 、Li7La3Zr 1.5 Nb 0.5 O 12 、Li7La3Zr 1.5 Ta 0.5 O 12 , Li 6.272 Ln3Z 1.7 W 0.3 O 12 or Li 5.39 Ga 1.61 Ln3Z 1.7 W 0.3 O 12 .
14. The solid electrolyte of claim 1, wherein the first porous layer comprises Li wherein 0.1≤x≤7, 0≤y≤2, and M is at least one of W, Ta, Te, or Nb. 7-x H x Ln3Z 2-y M y O 12 , and the second porous layer includes Li wherein 0≤x≤6.5, 0≤y≤2, and M is at least one of W, Ta, Te, or Nb 7-x H x Ln3Z 2-y M y O 12 . 15 . The solid electrolyte of claim 1 , wherein the first porous layer defines a surface of the solid electrolyte and has a porosity of 5% to 80%, and the second porous layer has a porosity of 1% to 50%.
16. The solid electrolyte of claim 1, wherein the first porous layer comprises Li wherein 0.1≤x≤7 7- x H x La3Zr2O 12 , and the second porous layer includes Li wherein 0≤x≤6.5 7-x H x La3Zr2O 12 .
17. The solid electrolyte of claim 1, wherein the first porous layer comprises Li wherein 0.1≤x≤6.75 6.75-x H x La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 , and the second porous layer includes Li wherein 0≤x≤6.5 7- x H x La3Zr2O 12 .
18. The solid electrolyte of claim 1, wherein the porous layer has a porosity of 5% to 60% based on the total volume of the porous layer.
19. The solid electrolyte of claim 1, wherein the inorganic lithium ion conductive membrane comprises an inorganic lithium ion conductor having a particle structure.
20. The solid electrolyte of claim 1, wherein the inorganic lithium ion conductive membrane comprises an inorganic lithium ion conductor having a columnar structure.
21. The solid electrolyte of claim 19, wherein the grains of the inorganic lithium ion conductor have a polyhedral shape.
22. A secondary battery comprising: positive electrode, The negative electrode, and A solid electrolyte as described in any one of claims 1 to 21 between the positive electrode and the negative electrode.
23. The secondary battery of claim 22, further comprising at least one of: a liquid electrolyte, a polymer electrolyte, or a lithium salt.
24. The secondary battery as claimed in claim 22, further comprising an ionic liquid.
25. The secondary battery as claimed in claim 22, further comprising a polymer ionic liquid. 26 . The secondary battery of claim 22 , further comprising a solid sulfide electrolyte between the negative electrode and the solid electrolyte.
27. The secondary battery of claim 26, wherein the solid sulfide electrolyte comprises Li2S-P2S5-LiX, wherein X is at least one of F, Cl, Br or I.
28. The secondary battery of claim 22, wherein the negative electrode comprises at least one of lithium metal or a lithium metal alloy.
29. A secondary battery as described in claim 22, wherein the surface of the solid electrolyte in contact with the negative electrode has a pore size larger than the surface of the solid electrolyte in contact with the positive electrode, and the pore size in the solid electrolyte decreases in a direction extending away from the negative electrode in the solid electrolyte, and the pore size is determined based on a cross-sectional scanning electron microscopy image.
30. The secondary battery of claim 22, wherein the secondary battery is configured to operate for more than 1000 cycles at a current density of 3 mA / cm2.
31. A method for preparing a solid electrolyte as claimed in any one of claims 1 to 21, the method comprising: a first acid treatment comprising acid-treating the inorganic lithium ion conductive membrane with an acid having a concentration greater than or equal to 0.1 molar and less than or equal to 5 molar to provide a first acid-treated product; and A first wash includes washing the first acid-treated product to provide a washed first acid-treated product to prepare the solid electrolyte.
32. The method of claim 31, further comprising preparing the inorganic lithium ion conductive membrane by combining an inorganic lithium ion conductor and a lithium compound to prepare a mixture, and heat treating the mixture.
33. The method of claim 32, wherein the lithium compound comprises at least one of lithium carbonate, lithium hydroxide or lithium oxide, and The amount of the lithium compound is 0.1 parts by weight to 10 parts by weight based on 100 parts by weight of the total weight of the inorganic lithium ion conductor and the lithium compound.
34. The method of claim 31, further comprising: a second acid treatment comprising acid treating the washed first acid treated product with an acid having a concentration greater than or equal to 0.1 molar and less than or equal to 5 molar to provide a second acid treated product; and a second wash comprising washing the product of the second acid treatment.
35. The method of claim 34, wherein the concentration of acid used in the second acid treatment is less than the concentration of acid used in the first acid treatment.
Citation Information
Patent Citations
Withdrawable circuit breaker
KR1020180106504A
Stabilized solid garnet electrolyte and methods thereof
US20160149260A1
Solid electrolyte and secondary battery
CN104272518A